2024
DOI: 10.3389/fendo.2023.1188870
|View full text |Cite
|
Sign up to set email alerts
|

Process analysis of the patient pathway for automated data collection: an exemplar using pituitary surgery

John G. Hanrahan,
Alexander W. Carter,
Danyal Z. Khan
et al.

Abstract: IntroductionAutomation of routine clinical data shows promise in relieving health systems of the burden associated with manual data collection. Identifying consistent points of documentation in the electronic health record (EHR) provides salient targets to improve data entry quality. Using our pituitary surgery service as an exemplar, we aimed to demonstrate how process mapping can be used to identify reliable areas of documentation in the patient pathway to target structured data entry interventions.Materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Recently, Hanrahan et al has used process mapping to comprehensively define the preoperative, perioperative and postoperative pathways for patients undergoing transsphenoidal surgery. 12 In the paper, they identified that pituitary ward round entries, pituitary clinical nurse specialist ward round entries and pituitary MDTs were critical data entry points that could be used for automated data entry. Our study builds on this previous work by investigating the educational resources that patients use before spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Hanrahan et al has used process mapping to comprehensively define the preoperative, perioperative and postoperative pathways for patients undergoing transsphenoidal surgery. 12 In the paper, they identified that pituitary ward round entries, pituitary clinical nurse specialist ward round entries and pituitary MDTs were critical data entry points that could be used for automated data entry. Our study builds on this previous work by investigating the educational resources that patients use before spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The process map was validated using a methodology described by Hanrahan et al . 12 The EHR of patients that presented with degenerative spinal disease (DSD) and were managed surgically between January and July 2022, at a tertiary-academic single centre in the UK was used. A sample size of 50 patients was chosen as it was deemed adequate to gain an in-depth understanding of the patient pathway.…”
Section: Methodsmentioning
confidence: 99%